Advances on the fast pyrolysis of biomass for the selective preparation of phenolic compounds - Hu, Bin; Zhang, Zhen-xi; Xie, Wen-luan; Liu, Ji; Li, Yang; Zhang, Wen-ming; Fu, Hao; Lu, Qiang (Fuel processing technology, 2022)
Biomass can be converted into various value-added products via the fast pyrolysis technique which is one of the main thermal conversion technologies and has gained widespread attention. Phenolic compounds are valuable products from biomass fast pyrolysis and can be widely used in energy, fuel, chemistry, and other industries. Lignin in lignocellulosic biomass is the major source of phenolic compounds, and some specific hydroxycinnamic structures (e.g., p-coumaric acids and ferulic acids) can also be converted into phenolics during pyrolysis. The formation of phenolic compounds is influenced by biomass materials, catalysts, and pyrolysis conditions. So far, many studies have been done to achieve the production of the mixed phenolics and/or the individual monophenolics through distinct pyrolysis processes. The present paper summarizes the general formation mechanism of phenolic compounds and provides an updated review of the selective preparation of mixed phenolics and individual monophenolics via biomass fast pyrolysis. The effects of major factors on their generation are also discussed in detail. The knowledge in this review is expected to be a reference to the selective preparation of phenolic compounds. [Display omitted] •Selective production of mixed phenolics and individual monophenolics was reviewed.•Phenolics mainly derive from the decomposition of the lignin component.•Hydroxycinnamic structures and holocellulose can also be converted into phenolics.•Catalysts and hydrogen donors play important roles in the formation of phenolics.